Kaidah المشقه تجلب التيسير dan Penerapannya dalam Hukum Keluarga - Nur Suci Alawiyah; Mhd Amar Adly; Heri Firmansyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Because Islamic law is not mentioned directly in the Qur'an and Hadith, interpretation and contextualization through ijtihad are often necessary. To achieve this, Islamic jurisprudence must be integrated with current conditions and societal demands. This must be done in accordance with maqasid al-syariah, namely the aim of overcoming legal problems faced by individuals (mukallaf). Sharia guarantees the welfare of every person and is adapted to their abilities. It is stated in a hadith in the hadith of the Prophet narrated by Bukhari which means: